Thermal process establishment of sauteed camaru (Gryllotalpa orientalis) in tin can - Carreon, H.R. William Sanchez; Acevedo, Teresita P. (2004)
ABSTRACT Evaluation of different formulations of sauteed Camaru (Gryllotalpa orientalis) was done to determine which formulation was the most acceptable to consumers. Sauteed Camaru of varying salt content (20g, 30g, and 40g per kilo of Camaru) was prepared and evaluated by a sensory panel using a simple preference ranking. The result of the ranking showed that the formulation having 30 grams of salt per kilo of Camaru is the most acceptable formulation to the panelists. Using the most acceptable formulation of sauteed Camaru, thermal process was determined. The average pH of the product was 4.67, classifying it as a low-acid product. The product was heat processed at 250°F for 40 minutes (trial 1). The thermal process was evaluated to be adequate to render the product commercially sterile. The adequacy of the thermal process was determined based on the heat resistance characteristics of the reference organism, Clostridium sporogenes, at 250°F (Stumbo 1973) and an order-of-the-process factor of 7. Cut-out tests results showed that the product would have a shelf life of one year or more. Sensory evaluation showed that the formulated product is acceptable in all its sensory attributes. The established process of 250°F for 40 minutes was verified by conducting another production run (trial 2). The results of the production run showed that the heat process at 250°F for 40 minutes is adequate to render the product commercially steri
Thesis (BSFT)--University of the Philippines, Diliman.
Keywords: Edible insects; Food, Canned